Meckel's diverticulum abscess in the elderly population: A case report. (February 2022) - Ioannidis, Aristeidis; Tzikos, Georgios; Papavasileiou, Ioanna; Touriki, Aikaterini-Vasiliki; Doutsini, Nektaria-Dimitra; Michalopoulos, Antonios; Paramythiotis, Daniel
Abstract: Introduction: and importance: Meckel's Diverticulum (MD) is the most usual congenital anatomic abnormality of the gastrointestinal tract. It is present in almost 2% of the population and it rarely becomes symptomatic in adults. Herein, we report a rare case of an elderly woman with MD, its diagnostic algorithm and treatment, pointing out the significance of this pathology in the differential diagnosis of right lower quadrant pain. Case presentation: A 75-year-old woman presented in the emergency department due to sudden right lower quadrant abdominal pain and fever. After a comprehensive clinical and imaging evaluation, a diagnostic laparoscopy under general was performed. The appendix presented without inflammation, and a MD abscess was found about 50cm from the ileocaecal valve. The resection of the MD abscess, the appendix and the gallbladder (due to synchronous chololithiasis) were performed. The patient had an uncomplicated post-operative course and she was discharged from hospital on the fifth postoperative day after having been fed and mobilized enough. Clinical discussion: A complicated MD can be a life-threatening situation. Generally, the MD cannot be easily diagnosed through obtaining patient's medical history, clinical examination and laboratory testing and it is undiagnosed to up to 60% of the cases, while it is usually an incidental finding during a diagnostic laparoscopy or laparotomy. Conclusion: Clinicians should be aware that MD complications in the elderly population can vary. However, having under consideration the very low but true possibility of the MD in the old age may lead to an early and accurate diagnosis. Highlights: Meckel's diverticulum rare in elderly. 3 different operations at the same time. The laparoscopic approach is the state of the art treatment.